Biocompatibility evaluation for the developed hydrogel wound dressing – ISO-10993-11 standards – in vitro and in vivo study. (30th November 2021) - Thanusha, A V; Koul, Veena
Abstract: Assessment of biocompatibility for the developed wound dressing plays a significant role in translational studies. In the present research work, a wound dressing has been developed using gelatin, hyaluronic acid and chondroitin sulfate using EDC as crosslinker in a specific manner. The characterized hydrogel wound dressing was evaluated for its biocompatibility studies by means of ISO-10993-11 medical device rules and standards. Various parameters like skin sensitization test, acute systemic toxic test, implantation study, intracutaneous reactivity test, in vitro cytotoxicity test and bacterial reverse mutation test, were evaluated and the results demonstrated its safety for the pre-clinical investigation.